Saint-Python Leterme Castle - Material created and... (Wikimedia Commons, 1908)
Carte postale ancienne issue de Wikimedia Commons. Titre: Saint-Python Leterme Castle. Photograph from 1908 by E.L.D. On this place of the Marais, which will later become the "Place du poilu", a shepherd's trailer with near it its probable owners. On the left the "Château Leterme". There is little change compared to the photographs from 1903. However the brewery (future town hall) has its entrance walled and its zinc chimney has disappeared. The house on his left was razed.
Droits : Licence Creative Commons Zero, Public Domain Dedication via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; gare; Château; Carte postale